“Where exactly do I fall?”: understanding intersectional marginalized identities through Asian Americans’ experiences - Zhang, Bin; Du, Wenqian; Chang, Bo (Frontiers in Psychology, 2024)
The purpose of this study was to explore the intersection of race, gender, and sexual orientation as they relate to the lived and educational experiences of Asian American female sexual minority (AAFSM) college students attending Midwestern universities in the U.S. To explore their experiences, qualitative research, as a scientific tool, was best suited to serve the goal of this study. We employed one of McCall’s (2005) three intersectionality methodological approaches—intra-categorical complexity—to guide the study. The first finding indicated that the AAFSM student participants had experienced intersectional objectifications, including racial, gendered, and sexual objectification. This finding answered our research question regarding what it is like to be AAFSM students attending predominantly White campuses in Midwestern universities. Our findings also showed that the participants intersectionally internalized racism, sexism, and heterosexism as strategies to avoid being ostracized, which in turn allowed society/institution to internalize these -isms as norms. The manifestations of intersectional internalizations reported by participants included racial stereotypes, Whitenization, stereotypical gender roles, gender norms, parental influence, and institutional influence. The findings also indicated that our participants had experienced intersectional blindness; consequently, their understandings of Asianness, womenness, and LGBTQness were affected. Another meaningful finding was that the racism, sexism, and heterosexism experiences of the AAFSM students were compounded and complex. The theme was best categorized as intersectional post-racism-(hetero)sexism. The findings regarding students’ experiences with intersectional internalizations, intersectional blindness, and intersectional post-racism-(hetero)sexism answered the remaining two research questions. We, then continuously discussed intersectional internalization; de-intersectional-internalization; re-intersectional-internalization; intersectional visibilities, connections, and representations; the implementation of intersectionality; and intersectionalism. Discussions and suggestions were presented for providing an intersectional inclusive campus environment for our participants who were AAFSMs attending Midwestern predominantly White universities. The discussions, as a milestone, provided meaningful suggestions for educators, administrators, and universities to effectively create an intersectional inclusive educational environment for AAFSMs.